2002
DOI: 10.1002/hyp.1089
|View full text |Cite
|
Sign up to set email alerts
|

Variability and trends in the annual snow‐cover cycle in Northern Hemisphere land areas, 1972–2000

Abstract: Abstract:This study investigated variability and trends in the annual snow-cover cycle in regions covering high-latitude and high-elevation land areas in the Northern Hemisphere. The annual snow-cover cycle was examined with respect to the week of the last-observed snow cover in spring (WLS), the week of the first-observed snow cover in autumn (WFS), and the duration of the snow-free period (DSF). The analysis used a 29-year time-series of weekly, visible-band satellite observations of Northern Hemisphere sno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
174
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(205 citation statements)
references
References 46 publications
30
174
0
1
Order By: Relevance
“…Changes of snow cover stability in Poland are more or less in agreement with these high-latitude and highelevation areas in the Northern Hemisphere: the lastobserved snow cover in spring shifted in these areas earlier by 3-5 days/decade and the duration of the snow-free period increased by 5-6 days/decade in 1972-2000, primarily due to earlier snow cover disappearance in spring (Dye 2002).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Changes of snow cover stability in Poland are more or less in agreement with these high-latitude and highelevation areas in the Northern Hemisphere: the lastobserved snow cover in spring shifted in these areas earlier by 3-5 days/decade and the duration of the snow-free period increased by 5-6 days/decade in 1972-2000, primarily due to earlier snow cover disappearance in spring (Dye 2002).…”
Section: Discussionsupporting
confidence: 57%
“…Changes of the seasonal snow cover in the area of Poland as well as in the whole world are already quite well-known (e.g., Gutzler and Rosen 1992;Groisman et al 1994;Walland and Simmonds 1997;Brown 2000;Dye 2002). Poland is located within the pointed zone by Brown and Mote (2009) where seasonal mean air temperatures are in the range of −5°t o +5°C; these areas showed the largest decreases in snow cover duration during the 1966-2007 period due to their high sensitivity to climate changes (Brown and Mote 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, several analyses over longer time periods than the sixteen years considered here have shown significant trends toward an earlier date of snow VICENTE-SERRANO ET AL. : SNOW COVER DISAPPEARANCE cover disappearance and a longer snow-free period in the Northern Hemisphere [Brown, 2000;Robinson et al, 1995;Dye, 2002;Laxon et al, 2003;Stone et al, 2002;Bamzai, 2003].…”
Section: Spatial Patterns Of Temporal Variability In the Date Of Snowmentioning
confidence: 99%
“…However, the snow-free period has also increased because the snowmelt date has advanced 9 -15 days in the last 30 years [Dye, 2002;Zhou et al, 2001;Serreze et al, 2000;Stone et al, 2002;Bamzai, 2003] due to the temperature increase observed at northern latitudes [Jones and Moberg, 2003]. In contrast, no particular trends have been found for the dates of snow onset [Bamzai, 2003;Dye, 2002], although Brown [2000] did show a widespread significant trend toward earlier dates of maximum snow depth over the 1955-1997 period in North America.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation